Penetapan Wilayah Adat dan Masyarakat Hukum Adat Desa Penyengat Kecamatan Sungai Apit Kabupaten Siak - Wahyu Damon Prakoso (Jurnal Hukum Respublica, 2020)
The problem that occurs is how the indigenous people of swamps interpret the lack of management territory, the loss of livelihood resources and organize themselves to seize opportunities for management rights. The problem of customary land and indigenous peoples above, the researchers felt the need to study more deeply on the Determination of Indigenous Areas and Customary Law Communities in Penyengat Village, Sungai Apit Subdistrict, Siak Regency, Based on the Minister of Home Affairs Regulation No. 52 of 2014 concerning Guidelines for the Recognition and Protection of Indigenous Peoples. This type of research is sociological, so the data source used is primary data from interviews, secondary data from libraries and tertiary data from dictionaries, media, and encyclopedias. Data collection techniques are done by observation, interviews, and literature review.